COMMEMORATION, MEANING, AND HERITAGE OF WESTERN AUSTRALIAN WAR MEMORIALS. - Stephens, John (School of People, Environment and Planning, 2006)
Recent widespread interest in commemoration has underlined the continuing role of Australian war memorials as sites of memory and places of community identity. These memorials are heavily contested sites at the confluence of diverse community meanings, memory and politics. Current challenges are to maintain the relevance of war memorials in the face of changing meaning and local planning circumstances. This paper discusses recent Western Australian research in collaboration with the Returned and Services League to study the contested meanings of war memorials, their design, setting and planning issues and recover them as significant heritage and markers of community identity and citizenship.